Enhancing students’ academic performance in Malaysian online distance learning institutions - Zahir Osman,; Wardah Mohamad,; Ratna Khuzaimah Mohamad,; Liana Mohamad,; Tuan Fatma Tuan Sulaiman,
The increasing number of learner failure rates are alarming in online distance learning. Previous studies have identified the factors that have contributed to online distance learning students’ failure as lack of time and lack of motivation. The purpose of this study is to develop a direct effect understanding of extrinsic motivation, intrinsic motivation, self-efficacy and time management on students’ academic performance in an online distance learning institution in Malaysia. The Structural Equation Model (SEM) was used to analyse the casual relationships between independent variables and dependent variables. The model was developed and later tested by adopting the Partial Least Square (PLS) procedure on data collected from a survey that yielded 210 usable questionnaires. The findings showed that extrinsic motivation, intrinsic motivation, self-efficacy and time management have a significant and positive influence on students’ academic performance in an online distance learning institution. The findings imply that the relationship amongst extrinsic motivation, intrinsic motivation, self-efficacy and time management on a student’s academic performance in an online distance learning institution will lead to the online distance learning institution’s low attrition rate. This study uses SmartPLS 2.0 and SPSS 18.0 to test the hypothesis and analyse respondents’ profile, respectively.